Recovery of Trypanosoma forattinii Coutinho and Pattoli from a Trinidadian rodent Encontro de Trypanosoma forattinii Coutinho & Pattoli em roedores de Trinidad - C. O. R. Everard; Octávio E. Sousa (Universidade de São Paulo, 1972)
Recovery of Trypanosoma forattinii from natural infected Oryzomys capito velutinus from Trinidad, is reported. Negative results were obtained with attempts to infect experimentally, several laboratories animals, silvatyc rodents of the same ecological area and several species of triatomids bugs. Positive results were obtained only by using O. capito velutinus born in laboratory. Relata-se o encontro de Trypanosoma forattinii, em exemplares de Oryzomys capito velutinus de Trinidad. Tentativas de isolamento em meio de NNN e de inoculação experimental em animais de laboratório, foram completamente negativas. Resultados positivos foram obtidos com inoculação de O. capito velutinus criados em laboratórios. As tentativas de infectar triatomíneos e roedores silvestres da mesma área foram igualmente negativas.